News Attention in a Mobile Era. Issue 2 (23rd March 2018) - Dunaway, Johanna; Searles, Kathleen; Sui, Mingxiao; Paul, Newly
Abstract: Mobile access to the Internet is changing the way people consume information, yet we know little about the effects of this shift on news consumption. Consuming news is key to democratic citizenship, but is attention to news the same in a mobile environment? We argue that attention to news on mobile devices such as tablets and smartphones is not the same as attention to news for those on computers. Our research uses eye tracking in two lab experiments to capture the effects of mobile device use on news attention. We also conduct a large-scale study of web traffic data to provide further evidence that news attention is significantly different across computers and mobile devices.